Proyecto de Titulación denominado, “Consumo de Alcohol y Drogas asociado al Rendimiento Académico en estudiantes de la carrera de Derecho/Universidad Estatal de Bolívar, periodo octubre 2023 – febrero 2024” - Llivi Ruilova, Danny Vicente (2024)
The Nursing program of the Faculty of Health and Human Sciences of the UEB, through the Degree Project called, “Alcohol and Drug Consumption Associated with Academic Performance in students of the Law program/State University of Bolívar , period October 2023 – February 2024”; by the students Janeth Marlene Cuji Pilco and Norma Yessica Lema Salazar, directed by Mgtr. María José Fierro; In the first part, they share information material with the purpose of raising awareness among the university community about this problem.